A Lassa Virus Live-Attenuated Vaccine Candidate Based on Rearrangement of the Intergenic Region - Yingyun Cai (American Society for Microbiology, 2020)
ABSTRACT Lassa virus (LASV) poses a significant public health problem within the regions of Lassa fever endemicity in Western Africa. LASV infects several hundred thousand individuals yearly, and a considerable number of Lassa fever cases are associated with high morbidity and lethality. No approved LASV vaccine is available, and current therapy is limited to an off-label usage of ribavirin that is only partially effective and associated with significant side effects. The impact of Lassa fever on human health, together with the limited existing countermeasures, highlights the importance of developing effective vaccines against LASV. Here, we present the development and characterization of a recombinant LASV (rLASV) vaccine candidate [rLASV(IGR/S-S)], which is based on the presence of the noncoding intergenic region (IGR) of the small (S) genome segment (S-IGR) in both large (L) and S LASV segments. In cultured cells, rLASV(IGR/S-S) was modestly less fit than wild-type rLASV (rLASV-WT). rLASV(IGR/S-S) was highly attenuated in guinea pigs, and a single subcutaneous low dose of the virus completely protected against otherwise lethal infection with LASV-WT. Moreover, rLASV(IGR/S-S) was genetically stable during serial passages in cultured cells. These findings indicate that rLASV(IGR/S-S) can be developed into a LASV live-attenuated vaccine (LAV) that has the same antigenic composition as LASV-WT and a well-defined mechanism of attenuation that overcomes concerns about increased virulence that could be caused by genetic changes in the LAV during multiple rounds of multiplication. IMPORTANCE Lassa virus (LASV), the causative agent of Lassa fever, infects several hundred thousand people in Western Africa, resulting in many lethal Lassa fever cases. No U.S. Food and Drug Administration-licensed countermeasures are available to prevent or treat LASV infection. We describe the generation of a novel LASV live-attenuated vaccine candidate rLASV(IGR/S-S), which is based on the replacement of the large genomic segment noncoding intergenic region (IGR) with that of the small genome segment. rLASV(IGR/S-S) is less fit in cell culture than wild-type virus and does not cause clinical signs in inoculated guinea pigs. Importantly, rLASV(IGR/S-S) protects immunized guinea pigs against an otherwise lethal exposure to LASV.